Acid Resistance of Enamel Subsurface Lesions Remineralized by a Sugar-Free Chewing Gum Containing Casein Phosphopeptide-Amorphous Calcium Phosphate - Iijima, Y.; Cai, F.; Shen, P.; Walker, G.; Reynolds, C.; Reynolds, E.C. (Caries research, 2004)
The aim of this clinical study was to investigate the acid resistance of enamel lesions remineralized in situ by a sugar-free chewing gum containing casein phosphopeptide-amorphous calcium phosphate nanocomplexes (CPP-ACP: Recaldent™). The study utilized a double-blind, randomized, crossover design with two treatments: (i) sugar-free gum containing 18.8 mg of CPP-ACP, and (ii) sugar-free gum not containing CPP-ACP as control. Subjects wore removable palatal appliances with insets of human enamel containing demineralized subsurface lesions and chewed the gum for 20 min 4 times per day for 14 days. After each treatment the enamel slabs were removed and half of each lesion challenged with acid in vitro for 8 or 16 h. The level of remineralization was determined using microradiography. The gum containing CPP-ACP produced approximately twice the level of remineralization as the control sugar-free gum. The 8- and 16-hour acid challenge of the lesions remineralized with the control gum resulted in 65.4 and 88.0% reductions, respectively, of deposited mineral, while for the CPP-ACP-remineralized lesions the corresponding reductions were 30.5 and 41.8%. The acid challenge after in situ remineralization for both control and CPP-ACP-treated lesions resulted in demineralization underneath the remineralized zone, indicating that the remineralized mineral was more resistant to subsequent acid challenge. The results show that sugar-free gum containing CPP-ACP is superior to an equivalent gum not containing CPP-ACP in remineralization of enamel subsurface lesions in situ with mineral that is more resistant to subsequent acid challenge.